Beryllium isotope variations recorded in the Adélie Basin, East Antarctica reflect Holocene changes in ice dynamics, productivity, and scavenging efficiency - Behrens, Bethany C.; Yokoyama, Yusuke; Miyairi, Yosuke; Sproson, Adam D.; Yamane, Masako; Jiménez-Espejo, Francisco J.; McKay, Robert M.; Johnson, Katelyn M.; Escutia, Carlota; Dunbar, Robert B. (Quaternary Science Advances, 2022)
The Adélie Basin is a relatively small (∼1600 km), semi-enclosed continental shelf bathymetric depression located adjacent to the Wilkes Subglacial Basin, a basin underlying a sector of the East Antarctic Ice Sheet that contains ∼3–4 m sea level equivalent of ice. Located within the Adélie Basin is a ∼184 m thick laminated sediment deposit, the Adélie Drift, ideal for examining regional changes in ice sheet and ocean dynamics. Here, we examine the ratio of reactive beryllium-10 to reactive beryllium-9 ((Be/Be)) in a marine sediment core obtained from the Adélie Drift to assess these changes during the Holocene epoch (11.7 ka BP to present). The (Be/Be) record provides insight into changes in freshwater input, primary productivity, and scavenging efficiency, while removing the influence of particle size on Be concentration. During the early Holocene, (Be/Be) ratios indicate increased meltwater discharge from ca. 11.7 to 10 ka BP, as grounded ice retreated from the Adélie Basin and adjacent bathymetric highs. After ∼10 ka BP, beryllium isotopes are influenced by scavenging efficiency and dilution controlled by ocean currents and accumulation rate, operating alongside meltwater input, suggesting there are additional factors to consider when using (Be/Be) as a proxy for ice shelf cover and glacial dynamics. Financial support for this study was provided by the Japan Society for the Promotion of Science ( JSPS ) KAKENHI ( 20H00193 ) to YY, JSPS Fellowship DC1 ( 20J21145 ) to BCB, and JSPS Post-Doctoral Fellowship (PE17712 and P18791) to ADS . RM was funded by the New Zealand Ministry of Business, Innovation and Employment through the Antarctic Science Platform ( ANTA1801 ). CE and FJJ-E acknowledges funding through Spanish Ministry of Science and Innovation (grant CTM2017-89711-C2-1-P ), co-funded by the European Union through FEDER funds.